Foods to fuel your muscles using glycemic index
Athletes need to fuel their muscles with foods that are high in carbohydrate. The glycemic index is a useful tool that measures how fast a particular carbohydrate will raise your blood sugar. The higher the glycemic i ndex, the faster the food will fuel your muscles. After physical activity it is best to eat foods that have a high or moderate glycemic i ndex so your muscles receive the energy quicker. On the other hand, before training you should eat foods with a lower glycemic i ndex so that the energy will last a longer time.